2000
DOI: 10.1097/00005768-200008000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in physical activity in a biracial cohort during adolescence

Abstract: The longitudinal data on physical activity collected in the NGHS cohort further confirm a dramatic decrease in the overall level of physical activity during the transition from childhood to adolescence. The consistency among the three methods indicate that both the AD and HAQ are useful tools for the assessment of activity levels in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
197
5
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 270 publications
(223 citation statements)
references
References 19 publications
15
197
5
6
Order By: Relevance
“…Overall, the data showed a dramatic decrease in the level of physical activity during the transition from childhood to adolescence (Kimm et al, 2000). The results showed that the level of girls' daily activity declined by 35% from ages 9-10 to 18-19 years, whereas the level of habitual activity declined by 83% (Kimm et al, 2000).…”
Section: Gender Differencesmentioning
confidence: 89%
See 3 more Smart Citations
“…Overall, the data showed a dramatic decrease in the level of physical activity during the transition from childhood to adolescence (Kimm et al, 2000). The results showed that the level of girls' daily activity declined by 35% from ages 9-10 to 18-19 years, whereas the level of habitual activity declined by 83% (Kimm et al, 2000).…”
Section: Gender Differencesmentioning
confidence: 89%
“…Of additional concern is the age-related decline in physical activity from childhood to adolescence, especially among females (Bradley, McMurray, Harrell, & Deng, 2000;Eaton et al, 2006;Gordon-Larsen et al, 2000;Grunbaum et al, 2004;Harrell et al, 1997;Kimm et al, 2000). Results from the 2005 national Youth Risk…”
Section: Gender Differencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessment of physical activity, developmental status and other demographic variables Habitual physical activity was assessed using a 3 d activity diary, in tandem with the 3 d food record (29) . Mean energy expenditure was represented as the number of minutes engaged in different metabolic equivalent (MET) activities across the day, expressed as MET-min/d.…”
Section: Dietary Assessmentmentioning
confidence: 99%